Processing of Emotion in Functional Neurological Disorder - Sojka, Petr; Bareš, Martin; Kašpárek, Tomáš; Světlák, Miroslav (Frontiers in Psychiatry, 2018)
Emotions have traditionally been considered crucial in the development of functional neurological disorder, but the evidence underpinning this association is not clear. We aimed to summarize evidence for an association between functional neurological disorder and emotions as formulated by Breuer and Freud in their conception of hysterical conversion. Based on a systematic literature search, we identified 34 controlled studies and categorized them into four groups: (i) autonomic arousal, (ii) emotion-motion interactions, (iii) social modulation of symptoms, and (iv) bodily awareness in FND. We found evidence for autonomic dysregulation in FND; convergent neuroimaging findings implicate abnormal limbic-motor interactions in response to emotional stimuli in FND. Our results do not provide enough empirical evidence for social modulation of the symptoms, but there is a clinical support for the role of suggestion and placebo in FND. Our results provide evidence for abnormal bodily awareness in FND. Based on these findings, we propose that functional neurological symptoms are forms of emotional reactions shaped into symptoms by previous experience with illness and possibly reinforced by actual social contexts. Additional research should investigate the effect of social context on the intensity of functional neurological symptoms and associated brain regions.